Palm leave manuscripts related to Traditional medicine available in the Library University of Jaffna –a preliminary study - Visakaruban, M.; Navaneethakrishnan, S. (Royal Asiatic Society of Sri Lanka, 2015)
Palm-leaf manuscripts are irreplaceable and considered as historically valuable research material. Library of the University of Jaffna have a remarkable collection of Palmyra palm leave manuscripts covering a wide range of subjects. These were kept in the archives section of this Library with limited access for scholars. Ayurveda and Siddha are well known traditional medical system. The basic concepts of the Siddha medicine are the same as those of Ayurveda. Siddha medicine is of Dravidian origin and has its entire literature in Tamil language. It is ascertained from records that 207 palm manuscripts have been collected and two volume of catalogue of these manuscripts were published by the library in 1992 and 1997. Based on survey of the collection of palm-leaf manuscripts available in the Library University of Jaffna, this study was carried out to find out the subject coverage and Physical condition of manuscripts related to Traditional medicine. Findings of this study revealed that among the entire collection of 207 palm leaf manuscripts, around half (109) were related to Traditional medicine. They have been identified under seven subject categories namely General (89), Pulipani Vaithiyam (4), Medical Dictionary (2), Maddu Vakadam (7), Akatthiyar Vaithiyam (4), Kai Vakadam (2), and Visakadi Vaithiyam (1). Among them one was written in Sanskrit and the rest in Tamil. Based on analysis of number of leaves, only three were below 10 leaves, 59 were 10 to 100, 25 were 100 to 200, 13 were 100 to 200 and four were above 300 leaves. Length of the leave varies from 10.5cm to 50cm. Physical condition of these manuscripts were almost good (79) and 14 were slightly damaged and 16 were badly damaged. The large manuscript contains 327 leaves. This study encourages depth researches in Traditional medicine.
Keywords: Traditional medicine; Palm leave manuscripts